Gaining insight from future mothers: A survey of attitudes and perspectives of childbirth. (December 2022) - Clemons, Janine H.; Payne, Deborah; Garrett, Nick; McAra-Couper, Judith; Farry, Annabel; Swift, Emma Marie; Stoll, Kathrin
Highlights: When asked their preference, most (91%) women chose vaginal birth over caesarean delivery. Birth choices made before pregnancy may be motivated by a woman's fear of birth. Choices of epidural analgesia and/or surgical birth are associated with a high fear of birth. Being born outside of New Zealand and/or having depression is associated with a high fear of birth. Abstract: Objective: To determine whether participant characteristics and/or birth preferences of future mothers are associated with a fear of birth. Design: A cross-sectional survey was used to determine if fear of birth could be profiled in specific participant characteristics and birth choices. Setting: Urban New Zealand university. Participants: A convenience sample of women (final n  = 339) who were < 40 years old, attending university, not pregnant nor had been pregnant but wished for at least one child in the future. Findings: Multivariable analysis identified a subset of four variables that were independently associated with the instrument Childbirth Fear Prior to Pregnancy (CFPP) measuring fear of birth (mean CFPP=38.0, SE=10.1). Preferences of birth by caesarean section ( n =32, mean CFPP=44.3, SE=1.8, p  < 0.0001), use of epidural analgesia ( n =255, mean CFPP=45.0, SE=1.1, p  < 0.0001), participants born outside of New Zealand ( n =123, mean CFPP=42.9, SE=1.4, p  < 0.0001), and participants who scored > 20 ('severe') for depression on DASS-21 scale ( n =11, mean CFPP=44.8, SE=1.7, p  < 0.0001) were all positively associated with CFPP. Post-hoc analyses revealed that mean CFPP was higher for those that perceived birth technologies as easier, safer, necessary, and required. Conclusions: Women born outside of New Zealand and/or suffering 'severe' depression were more likely to have a fear of birth. Fear of birth was associated with the participants choices towards medicalised childbirth. Familiarising women with the provision of maternity care in New Zealand and identifying mental health status early could reduce fear of birth and possibly support the vaginal birth intentions of future parents.